(untitled) (University of Khartoum Engineering Journal, 2022)
An assessment was conducted to delineate the level of industrial hygiene and occupational safety in Khartoum North to identify critical tasks, responsible parties and required resources for an industrial hygiene and occupational safety. Assessment instruments used in this research study included an on-line survey, review of periodic environmental survey reports and documents, walk through survey and personal interviews. A cross- sectional study was designed to assess industrial hygiene and occupational safety practices in Khartoum north. The study was conducted on 32 food industries in Khartoum North industrial area. Assessment of some physical hazards mainly, noise, lighting and heat stress in those plants revealed that 74% of the inspected work places are exposed to high noise level, and 72.2% do not fulfill the industrial lighting requirements. Chemical hazards were attributed to Chemical detergents used in cleaning operations and disinfection of process areas. Back injuries represent the most reported occupational health related problems mainly caused by Slips and strips. The study revealed that only31.25% of the plants have a Safety supervisor, and 3.2% of those plants conduct a pre-employment medical examination. Absence of safety education and non-availability of personal protective equipment were the most reported reasons for not using PPE. It was also found that workers do not have background about their jobs related hazards. Other findings show that monitoring is not implemented regularly and properly by the concerned authorities. Standardized safety records were not kept or maintained. The study concluded that emergency procedures, personal protective equipment, first aid and safety, facilities in addition to indoor environment could be classified as unsatisfactory